Effect of salt intake on beat‐to‐beat blood pressure nonlinear dynamics and entropy in salt‐sensitive versus salt‐protected rats. Issue 11 (10th June 2016) - Fares, Souha A.; Habib, Joseph R.; Engoren, Milo C.; Badr, Kamal F.; Habib, Robert H.
Abstract: Blood pressure exhibits substantial short‐ and long‐term variability (BPV). We assessed the hypothesis that the complexity of beat‐to‐beat BPV will be differentially altered in salt‐sensitive hypertensive Dahl rats (SS) versus rats protected from salt‐induced hypertension (SSBN13) maintained on high‐salt versus low‐salt diet. Beat‐to‐beat systolic and diastolic BP series from nine SS and six SSBN13 rats (http://www.physionet.org ) were analyzed following 9 weeks on low salt and repeated after 2 weeks on high salt. BP complexity was quantified by detrended fluctuation analysis (DFA), short‐ and long‐range scaling exponents ( α S and α L ), sample entropy (SampEn), and traditional standard deviation (SD) and coefficient of variation (CV(%)). Mean systolic and diastolic BP increased on high‐salt diet ( P  < 0.01) particularly for SS rats. SD and CV(%) were similar across groups irrespective of diet. Salt‐sensitive and ‐protected rats exhibited similar complexity indices on low‐salt diet. On high salt, (1) SS rats showed increased scaling exponents or smoother, systolic ( P  = 0.007 [ α L ]) and diastolic ( P  = 0.008 [ α L ]) BP series; (2) salt‐protected rats showed lower SampEn (less complex) systolic and diastolic BP ( P  = 0.046); and (3) compared to protected SSBN13 rats, SS showed higher α L for systolic ( P  = 0.01) and diastolic ( P  = 0.005) BP. Hypertensive SS rats are more susceptible to high salt with a greater rise in mean BP and reduced complexity. Comparable mean pressures in sensitive and protective rats when on low‐salt diet coupled with similar BPV dynamics suggest a protective role of low‐salt intake in hypertensive rats. This effect likely reflects better coupling of biologic oscillators. Abstract : We investigated the non‐linear dynamical properties of blood pressure variability, specifically complexity analysis and detrended fluctuation analysis (DFA), of the systolic and diastolic blood pressure time series in 9 salt sensitive and 6 protected rats. We showed that salt sensitive rats exhibit varying non linear BP dynamics compared to protected rats (smoother time series), irrespective of diet; we also showed the differential impat of salt intake on complexity and DFA metrics in both strains of rats.